EFFECT OF FAST FOOD CONSUMPTION WITH OBESITY OCCURRENCE OF TEENAGER IN INDRAMAYU - Depi Yulyanti; Muhamad Fauzi; Heri Sugiarto; Rudiansyah Rudiansyah; Riski Andriyani (JURNAL KESEHATAN INDRA HUSADA, 2021)
Fast food is characterized by an imbalanced nutritional content. Most are high in calories, but very low in fiber. Fast food is a major factor affecting obesity. Based on the 2013 Riskesdas the prevalence of obesity was 28.9%, while the results of the 2018 Riskesdas data showed that the prevalence of obesity had reached 52.8%. Based on these data, it is known that there is an increase in obesity cases by 1.36%. The purpose of this study was to determine the relationship between fast food consumption and obesity in adolescents. This research method uses analytical research design with a cross sectional approach. The sampling technique used accidental sampling with a total of 94 samples calculated using the Slovin formula. The research instrument used a questionnaire, research sites in vocational high schools in Indramayu District in 2019. The analysis used univariate and bivariate analysis was carried out by using the Chi-Square Test. The results of this study indicate that there is an effect between consumption of fast food and the incidence of obesity with a value of P = 0.000. The next researcher should examine family support and the school environment for fast food consumption behavior in teenagers.